Effect of Andaliman Fruit Extract (Zanthoxylum acanthopodium DC.) on The Liver of Tartrazine Induced Rat (Rattus norvegicus L.) - Juandi AlGani Sika; Husnarika Febriani; Syukriah Syukriah (Journal of Agromedicine and Medical Sciences, 2024)
Effect of tartrazine as synthetic food coloring that is consumed for long time has a toxic effect by free radicals in large quantities creating an imbalance in body and triggering disturbances, namely liver function. Free radicals can be minimized with antioxidants so they can reduce free radicals in body. Antioxidants can be found in all types of plants, one of which is Andaliman fruit. The purpose of this study was to determine effect ethanol extract of Andaliman fruit on SGOT-SGPT levels and histology of tartrazine-induced white rats. The research design used 25 white rats with 5 treatments and 5 replications for 30 days. Negative control group induced by 1% CMC, positive control induced by tartrazine 15 mg/kg BW, treatment groups 1, 2, 3 induced by tartrazine 15 mg/kg BW and ethanol extract andaliman fruit 150 mg/kg BW, 300 mg/kg BW, and 450 mg/kg BW. The stages in this study were screening for phytochemicals, total flavonoids and antioxidant activity as well as measurement of SGOT-SGPT levels and observation of liver histology. Data were analyzed using one way Anova and Duncan's further test. Results showed that phytochemical screening of Andaliman fruit extract contained flavonoids, terpenoids, steroids and tannins. Total flavonoid content in extract was 7.8163 mgQE/g extract. And level antioxidant activity in the extract has an IC50 value of 102.35 ppm. The results of this study also showed that the extract had an effect on decreasing levels of SGOT-SGPT and could minimize liver histological damage after being induced by tartrazine. Keywords: Andaliman, tartrazine, SGOT-SGPT, liver histology